Job engagement among nonstandard workers in Singapore. - Quek, Leanne Ying Ying. (2011)
Organisations have increasingly turned to nonstandard work relationships to cope with the increased emphasis on cost restructuring and flexibility in today’s competitive work environment. In light of these developments, it is important to gain a comprehensive appreciation of these nonstandard workers to gain optimal performance within the workforce. Previous research focused mainly on the commitment and job satisfaction levels of nonstandard workers, with frequent comparisons being made with respect to their standard counter parts. A study by Ashford, George and Blatt (2007) highlighted that the differences in job mortality would lead to variations in the behaviours and attitudes of both standard and nonstandard workers. Job engagement is an ideal barometer to measure such behaviours, characterised by the willingness to learn and perform at the job. Consequently, exploring on the area of job engagement will greatly contribute to the current understandings of nonstandard work relationships. Thus, our study involves an assessment of the relationship between work attributes and job engagement. Moderate correlations were found between the three identified work-design attributes, and physical, cognitive and emotional employee job engagements. Our analysis further yielded high positive relationships, between components of job engagement with the selected work-design attributes: work methods autonomy, feedback from job and social support. In addition, a partial mediation relationship was also detected between social support and all components of job engagement, with proactive behaviours as mediating factors.